The dynamics of a levitated cylindrical permanent magnet above a superconductor - Schreiner, Michael (Revista Matemática Complutense, 2003)
When a permanent magnet is released above a superconductor, it is levitated. This is due to the Meissner-effect, i.e. the repulsion of external magnetic fields within the superconductor. In experiments, an interesting behavior of the levitated magnet can be observed: it might start to oscillate with increasing amamplitude and some magnets even reach a continuous rotation. In this paper we develop a mathematical model for this effect and identify by analytical methods as well with ¯nite element simulations two reasons for the described behavior of the levitated magnet. It is shown, that the oscillations of the magnet are due to inhomogeneities of the magnetization within the magnet, whereas the continuous rotations are due to temperature gradients of the surrounding air.